Buffering management schemes for optical variable length packets under limited packet sorting - Tan, Choo Peng; Castanon, Gerardo; Chien, Su Fong; You, Ah Heng; Low, Andy L. Y. (SPRINGER, 2006)
This paper studies several buffering strategies for optical packet switching (OPS) under limited packet sorting. Three schemes, which are able to sort newly arrived packets based on packet's length as well as capability of finding the minimum buffer occupancy, are analyzed and compared. Results show that all three proposed schemes could improve OPS performance considerably in terms of probability of packet loss (PPL) and probability of information loss (PIL). In addition, the simulation results show that not all the newly arrived packets need to be sorted in order to obtain minimum packet loss probability. Since the amount of packets and thus the packet processing time is significant in OPS, it is possible that not all the packets can be processed using one of the buffering strategies. An important finding of this paper is that if only 10% of the packets are sorted, the PPL is comparable to the minimum packet loss value obtained when 100% of the packets are sorted.